Upaya Senam Kaki untuk Mencegah Resiko Komplikasi Pada Tn.S dengan Diabetes Mellitus - Utami, Senja Putri; , Supratman, Ph. D (2017)
Type 2 diabetes mellitus is a common endocrine disease. Chronic complications of diabetes mellitus in Indonesia consist of neuropathy 60%, 20,5% of coronary heart disease, diabetic ulcers 15%, 10% retinopathy, nephropathy 7,1%. This can occur because of the knowledge and behavior of those who are less good. To write a scientific journal aimed to know the nursing problems in patients with diabetes and teaches leg exercise in the effort to prevention of secondary complications in patients with diabetes mellitus. The authors used the descriptive method with case study approach is the scientific method is to collect data, analyze data, and draw conclusions in Puskesmas. In obtaining the data the authors use several ways include collecting data through observation, physical examination, interview, documentation study journals and books. The results obtained in patients with type 2 diabetes is a major problem in tissue perfusion disturbances (tingling) and risk of complications. To solve the problem, author teaches leg exercise. Leg exercise can help improve peripheral circulation and control blood sugar levelsso as to prevent complications that will occur. Keywords: diabetes mellitus, complications, diabetic foot gymnastics.